Analysis of Waste Management in Batang Hari Regency - Mekarisce, Arnild Augina; Saragih, Yaya Intan Aminita; Solida, Adila; Lesmana S, Oka; Samsidar, Samsidar (Jurnal Kesmas Jambi, 2026)
The waste problem in Batang Hari Regency continues to increase in line with population growth, with a daily volume of around 31 tons and 87% of temporary waste storage sites being illegal. This condition has an impact on public health, aesthetics, and environmental pollution. Waste management analysis is needed to improve management effectiveness, but such analysis has not been conducted comprehensively with involvement of stakeholders. The research aims to explore and provide an in-depth understanding of the social phenomenon being observed, focusing on detailed descriptions of field conditions. This research uses qualitative case study design. Data was collected through in-depth interviews, observations, and document reviews involving 10 informants. Data analysis was conducted using content analysis techniques, and data validity was ensured through triangulation of sources. The results show that waste management planning has been developed but has not been optimally implemented due to limitations in budget, fleet, and manpower. The implementation of collection and transportation is constrained by facilities and low public awareness of waste sorting. Evaluations are conducted but are not consistent, especially regarding illegal temporary waste storage sites. Follow-up actions in the form of socialization, additional facilities, and technical improvements have been carried out, but they have not completely resolved the problem. The implementation of management plays a crucial role in identifying weaknesses and promoting continuous improvement. Strengthening the budget, adding facilities, increasing the capacity of personnel, and active community participation are urgently needed to make waste management more optimal, sustainable, and positively impact health and the environment.